Necessity and the Unexpected: SoTL Student-Faculty Collaboration in Writing Program Research - Kathryn Wymer; Carolyn Fulford; Nia Baskerville; Marisha Washington (International Journal for the Scholarship of Teaching and Learning, 2012)
This essay describes how a team of faculty members and undergraduate students worked together to investigate key questions about the experiences students at our campus face as they transition from high school to college. We describe the process we employed in starting our project, and we draw some conclusions about the unexpected positive outcomes of our SoTL student-faculty partnership.